Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Let's start with question 13.
### 13. If [tex]\((k+2)x^2 - (k+2)x - 1 = 0\)[/tex] has one real root, then the value of [tex]\(k\)[/tex] is:
To determine the values of [tex]\(k\)[/tex] for which the given quadratic equation has one real root, we need to set the discriminant of the quadratic equation to zero. The general form of a quadratic equation is [tex]\(ax^2 + bx + c = 0\)[/tex], with the discriminant given by [tex]\(\Delta = b^2 - 4ac\)[/tex].
For the given equation [tex]\((k+2)x^2 - (k+2)x - 1 = 0\)[/tex], let's identify the coefficients:
- [tex]\(a = k + 2\)[/tex]
- [tex]\(b = -(k + 2)\)[/tex]
- [tex]\(c = -1\)[/tex]
The discriminant [tex]\(\Delta\)[/tex] is calculated as:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values:
[tex]\[ \Delta = [-(k+2)]^2 - 4(k+2)(-1) \][/tex]
Simplify the discriminant:
[tex]\[ \Delta = (k+2)^2 - 4(k+2)(-1) \][/tex]
[tex]\[ \Delta = (k+2)^2 + 4(k+2) \][/tex]
[tex]\[ \Delta = (k+2)^2 + 4(k+2) \][/tex]
[tex]\[ \Delta = (k+2)[(k+2) + 4] \][/tex]
[tex]\[ \Delta = (k+2)(k+2+4) \][/tex]
[tex]\[ \Delta = (k+2)(k+6) \][/tex]
For the quadratic equation to have exactly one real root, the discriminant must be equal to zero:
[tex]\[ (k+2)(k+6) = 0 \][/tex]
Solving for [tex]\(k\)[/tex]:
[tex]\[ k+2 = 0 \quad \text{or} \quad k+6 = 0 \][/tex]
[tex]\[ k = -2 \quad \text{or} \quad k = -6 \][/tex]
Thus, the values of [tex]\(k\)[/tex] that make the equation have one real root are [tex]\(-2\)[/tex] and [tex]\(-6\)[/tex]. The answer is:
C. -6 or -2
---
### 14. The simplified form of [tex]\(\frac{(a+b)^2 - 1}{a+b+1}\)[/tex] is:
First, let's rewrite the numerator and the denominator:
[tex]\[ \text{Numerator: } (a+b)^2 - 1 \][/tex]
[tex]\[ \text{Denominator: } a+b+1 \][/tex]
The numerator [tex]\((a+b)^2 - 1\)[/tex] can be factored as a difference of squares:
[tex]\[ (a+b)^2 - 1 = (a+b)^2 - 1^2 = [(a+b) - 1][(a+b) + 1] \][/tex]
[tex]\[ (a+b)^2 - 1 = (a+b-1)(a+b+1) \][/tex]
So, the expression becomes:
[tex]\[ \frac{(a+b-1)(a+b+1)}{a+b+1} \][/tex]
We can cancel out the common factor [tex]\(a+b+1\)[/tex] in the numerator and the denominator:
[tex]\[ \frac{(a+b-1)(a+b+1)}{a+b+1} = a+b-1 \][/tex]
Thus, the simplified form of the expression is:
D. [tex]\(a+b-1\)[/tex]
### 13. If [tex]\((k+2)x^2 - (k+2)x - 1 = 0\)[/tex] has one real root, then the value of [tex]\(k\)[/tex] is:
To determine the values of [tex]\(k\)[/tex] for which the given quadratic equation has one real root, we need to set the discriminant of the quadratic equation to zero. The general form of a quadratic equation is [tex]\(ax^2 + bx + c = 0\)[/tex], with the discriminant given by [tex]\(\Delta = b^2 - 4ac\)[/tex].
For the given equation [tex]\((k+2)x^2 - (k+2)x - 1 = 0\)[/tex], let's identify the coefficients:
- [tex]\(a = k + 2\)[/tex]
- [tex]\(b = -(k + 2)\)[/tex]
- [tex]\(c = -1\)[/tex]
The discriminant [tex]\(\Delta\)[/tex] is calculated as:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
Substituting the values:
[tex]\[ \Delta = [-(k+2)]^2 - 4(k+2)(-1) \][/tex]
Simplify the discriminant:
[tex]\[ \Delta = (k+2)^2 - 4(k+2)(-1) \][/tex]
[tex]\[ \Delta = (k+2)^2 + 4(k+2) \][/tex]
[tex]\[ \Delta = (k+2)^2 + 4(k+2) \][/tex]
[tex]\[ \Delta = (k+2)[(k+2) + 4] \][/tex]
[tex]\[ \Delta = (k+2)(k+2+4) \][/tex]
[tex]\[ \Delta = (k+2)(k+6) \][/tex]
For the quadratic equation to have exactly one real root, the discriminant must be equal to zero:
[tex]\[ (k+2)(k+6) = 0 \][/tex]
Solving for [tex]\(k\)[/tex]:
[tex]\[ k+2 = 0 \quad \text{or} \quad k+6 = 0 \][/tex]
[tex]\[ k = -2 \quad \text{or} \quad k = -6 \][/tex]
Thus, the values of [tex]\(k\)[/tex] that make the equation have one real root are [tex]\(-2\)[/tex] and [tex]\(-6\)[/tex]. The answer is:
C. -6 or -2
---
### 14. The simplified form of [tex]\(\frac{(a+b)^2 - 1}{a+b+1}\)[/tex] is:
First, let's rewrite the numerator and the denominator:
[tex]\[ \text{Numerator: } (a+b)^2 - 1 \][/tex]
[tex]\[ \text{Denominator: } a+b+1 \][/tex]
The numerator [tex]\((a+b)^2 - 1\)[/tex] can be factored as a difference of squares:
[tex]\[ (a+b)^2 - 1 = (a+b)^2 - 1^2 = [(a+b) - 1][(a+b) + 1] \][/tex]
[tex]\[ (a+b)^2 - 1 = (a+b-1)(a+b+1) \][/tex]
So, the expression becomes:
[tex]\[ \frac{(a+b-1)(a+b+1)}{a+b+1} \][/tex]
We can cancel out the common factor [tex]\(a+b+1\)[/tex] in the numerator and the denominator:
[tex]\[ \frac{(a+b-1)(a+b+1)}{a+b+1} = a+b-1 \][/tex]
Thus, the simplified form of the expression is:
D. [tex]\(a+b-1\)[/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.